Reproductive Life Planning in Adolescents - Boyle, Jacqueline A.; Yimer, Nigus Bililign; Hall, Jennifer; Walker, Ruth; Jack, Brian; Black, Kirsten (Seminars in Reproductive Medicine, 2021)
Unplanned pregnancy in adolescents contributes to the burden of disease, mortality, and health and educational disparities experienced by young people during this vulnerable period between childhood and adulthood. Reproductive life planning (RLP) is an approach that has been endorsed and adopted internationally, which prompts individuals and couples to set personal goals regarding if and when to have children based on their own personal priorities. This review discusses RLP tools, their acceptability, effectiveness, and issues in implementation across different contexts, with a specific focus on how RLP has been applied for adolescents. While a range of RLP tools are available and considered acceptable in adult populations, there is minimal evidence of their potential benefits for adolescent populations. Online platforms and information technology are likely to promote reach and implementation of RLP interventions in adolescents. Consideration of the socioecological contexts where adolescent pregnancies are more common should be integral to much needed future work that explores RLP interventions in adolescents.
Keywords: adolescents; reproductive life planning; pregnancy; sexual and reproductive health